Does health service utilisation vary by remoteness? South Australian population data and the Accessibility and Remoteness Index of Australia - Kerena A. Eckert; Anne W. Taylor; David Wilkinson (Elsevier, 2004)
Abstract Objective: To compare rates of self‐reported use of health services between rural, remote and urban South Australians. Methods: Secondary data analysis from a population‐based survey to assess health and well‐being, conducted in South Australia in 2000. In all, 2, 454 adults were randomly selected and interviewed using the computer‐assisted telephone interview (CATI) system. We analysed health service use by Accessibility and Remoteness Index of Australia (ARIA) category. Results:There was no statistically significant difference in the median number of uses of the four types of health services studied across ARIA categories. Significantly fewer residents of highly accessible areas reported never using primary care services (14.4% vs. 22.2% in very remote areas), and significantly more reported high use (≥6 visits, 29.3% vs. 21.5%). Fewer residents of remote areas reported never attending hospital (65.6% vs. 73.8% in highly accessible areas). Frequency of use of mental health services was not statistically significantly different across ARIA categories. Very remote residents were more likely to spend at least one night in a public hospital (15.8%) than were residents of other areas (e. g. 5.9% for highly accessible areas). Conclusion: The self‐reported frequency of use of a range of health services in South Australia was broadly similar across ARIA categories. However, use of primary care services was higher among residents of highly accessible areas and public hospital use increased with increasing remoteness. There is no evidence for systematic rural disadvantage in terms of self‐reported health service utilisation in this State.